The Algorithmic Dilemma: Online Gambling Blocking and Data Privacy in Indonesia's E-Government - Vanessa Riarta Atmaja; Rina Shahrullah; Ampuan Situmeang (Faculty of Law Universitas Jenderal Soedirman, 2026)
The rapid proliferation of online gambling in Indonesia has prompted the Ministry of Communication and Informatics to implement large-scale algorithmic blocking measures, creating a critical tension between cybersecurity enforcement and citizen data protection. This study investigates the unintended consequences of these automated blocking mechanisms on government digital infrastructure that hosts personal data. Using normative legal research methodology with a conceptual approach grounded in Gustav Radbruch's legal philosophy which emphasizes. The research analyzes primary legal materials, including the Electronic Information and Transactions Law and implementing regulations, supplemented by secondary data from policy documents and case studies of breached government websites. Results demonstrate that while algorithmic blocking has successfully reduced gambling site accessibility by over 80%, it has simultaneously compromised data security indiscriminately blocking compromised government portals without adequate due process mechanisms. The absence of transparent algorithmic criteria in the TRUST+Positif system and the lack of procedural safeguards have created legal uncertainty and disproportionate impacts on public service delivery. The study concludes that Indonesia's current approach prioritizes technical utility over justice and legal certainty, necessitating regulatory reforms that balance cybersecurity objectives with constitutional privacy protections through precision-based blocking, algorithmic transparency requirements, and independent oversight mechanisms to ensure digital governance that respects fundamental rights while effectively combating online gambling.